Can small-sided games assess the training-induced aerobic adaptations in elite football players? - Riboli, A.; Dellal, A.; Esposito, F.; Coratella, G. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: The aim of this study was to investigate whether or not SSGs could be used to evaluate the aerobic fitness status and the longitudinal training-induced adaptations in football players. Additionally, the capacity of SSGs to recreate the official match demands was investigated. METHODS: Twenty-five elite football players were monitored. Total distance (TD), high-speed running, very high-speed running, sprint and accelerations plus decelerations distance were measured during 20 SSGs formats and 25 official-matches; in SSGs, average heart rate was also collected. During submaximal Yo-Yo test, heart rate at peak exercise, heart rate post-60s recovery and rate of perceived exertion were collected. Coefficient of variation, interclass correlation-coefficient and correlation-coefficient analysis were used to calculate validity, reliability, construct validity and, internal and external responsiveness of SSGs demands. RESULTS: In SSGs, a small variability (~6.0%) with moderate reliability (~0.542 to ~0.663) was found in TD and heart rate, while a high variability (~20.8% to ~60.3%) with poor to moderate reliability (~0.358 to ~0.605) was observed in the other metrics; in submaximal Yo-Yo, heart rate showed small variability (~3.7%) with good reliability (~0.933 to ~0.916). The SSGs demands showed poor internal and external responsiveness (P>0.05) to the training-induced aerobic adaptations as assessed by submaximal Yo-Yo. The construct validity of SSGs showed overall large to very large correlations (r=0.53 to 0.90, P<0.05) between SSGs and official match demands across the season. CONCLUSIONS: SSGs should not replace standardized field tests to detect the training-induced aerobic adaptations. However, SSGs could be confidently used to recreate specific contextual factors in elite football players.